Efficacy of aminophylline in the treatment of acute asthma exacerbation in children - (:unkn) unknown (ELSEVIER SCIENCE INC, 1998)
Background: The role of aminophylline (ethylene diamine salt of theophylline) in the treatment of acute exacerbation of asthma has not been well established in children. Objective: The aim of the study was to determine the additional therapeutic benefit of intravenous aminophylline in the treatment of children hospitalized for acute asth matic exacerbation and treated with inhaled bronchodilators and glucocorticoid therapy. Methods: Thirty-eight children aged from 2 to 16 years (mean age 5.64 +/- 3.31), admitted for acute exacerbation of asthma, participated in a prospective, randomized, double-blind, placebo-controlled study. All the subjects received methylprednisolone, administered intravenously, and nebulized salbutamol. The treatment group received intravenous aminophylline therapy and the placebo group received 0.9% saline solution for 24 hours. Results: The number of salbutamol nebulizations needed and the clinical asthma scoring were recorded both at onset and at the end of 24 hours. There was no significant difference in either the mean number of nebulizations or the clinical asthma scores between the two groups (P = .7843, P = .8452). Conclusion: Intravenous aminophylline (ethylene diamine salt of theophylline) demonstrated no additional beneficial effect to the combination of P adrenergic agonists and glucocorticoid treatment in acute asthma attack in children.
Keywords: THEOPHYLLINE; ALBUTEROL; BENEFIT